2011
DOI: 10.5423/ppj.2011.27.3.291
|View full text |Cite
|
Sign up to set email alerts
|

RT-PCR Detection of Five Quarantine Plant RNA Viruses Belonging to Potyand Tospoviruses

Abstract: In order to detect quarantine plant viruses, we developed reverse transcription-polymerase chain reaction (RT-PCR) primer pairs for five single-stranded (ss) plant RNA viruses that are not currently reported in Korea but could be potential harmful plant viral pathogens. Three viruses such as Chilli veinal mottle virus (ChiVMV), Colombian datura virus (CDV), and Tobacco etch virus (TEV) belong to the genus Potyvirus while Chrysanthemum stem necrosis virus (CSNV) and Iris yellow spot virus (IYSV) are members of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…RT-PCR was performed using the RevertAid RT Reverse Transcription Kit (Thermo Fischer Scientific, USA) targeting the N gene. The resultant cDNA was used for PCR amplification using the KAPA2G Fast Hot Start ReadyMix Kit (KAPA Biosystems, USA) and N gene-specific primers (IYSV_2F: 5'-GGCGGTCCTCTCATCTTACTG-3' and IYSV-NCP2_R: 5'-GAAGTTCCAGGAGTGCATTTAGTC-3') (Lee et al, 2011) under the following cycling conditions: initial denaturation at 95°C for 2 min; 35 cycles of 94°C for 15 s (denaturation step), 57°C for 15 s (annealing step), and 72°C for 15 s (extension step), followed by a 5-min incubation period at 72°C. PCR products were analyzed by *Corresponding author.…”
Section: Rna Extraction and Rt-pcrmentioning
confidence: 99%
“…RT-PCR was performed using the RevertAid RT Reverse Transcription Kit (Thermo Fischer Scientific, USA) targeting the N gene. The resultant cDNA was used for PCR amplification using the KAPA2G Fast Hot Start ReadyMix Kit (KAPA Biosystems, USA) and N gene-specific primers (IYSV_2F: 5'-GGCGGTCCTCTCATCTTACTG-3' and IYSV-NCP2_R: 5'-GAAGTTCCAGGAGTGCATTTAGTC-3') (Lee et al, 2011) under the following cycling conditions: initial denaturation at 95°C for 2 min; 35 cycles of 94°C for 15 s (denaturation step), 57°C for 15 s (annealing step), and 72°C for 15 s (extension step), followed by a 5-min incubation period at 72°C. PCR products were analyzed by *Corresponding author.…”
Section: Rna Extraction and Rt-pcrmentioning
confidence: 99%
“…However, the disadvantages of ELISA [9,10] in quarantine viruses make it unreliable for the detection and accurate diagnosis of quarantine viruses [7,11]. To speed the diagnosis and shorten the inspection period, polymerase chain reaction (PCR) method has been widely used [12][13][14][15][16]. The use of PCR to diagnose PMTV has been reported [17][18][19].…”
mentioning
confidence: 99%
“…However, its false positive reaction makes it difficult to conduct a precise diagnosis and quarantine examination, so methods with a higher detection capability are needed to detect a very tiny amount of viruses in a few infected seeds among a huge number of seeds [6,7]. In this study, the polymerase chain reaction (PCR) method, which had been found in a study to have a high degree of safety and was thoroughly studied recently as a quarantine examination method, was reviewed [8][9][10][11][12]. However, the following important problems were found.…”
mentioning
confidence: 99%